A REGULARIZED TRACE FORMULA FOR DIFFERENTIAL EQUATIONS WITH TRACE CLASS OPERATOR COEFFICIENTS - Albayrak, Inci; Koklu, Kevser; Bayramov, Azad (ROCKY MT MATH CONSORTIUM, 2010)
We will obtain a formula for the regularized trace of the differential equation of the second order with trace class operator coefficient.
Keywords: Self-adjoint operator; resolvent; spectrum; trace; Mathematics